Orbit of Galactic Globular Cluster of NGC 7089, NGC 7099, NGC 1851, Pal 1, and Pal 2 Around the Milky Way Galaxy Constructed from the Gaia EDR3 (Journal of Nepal Physical Society, 2021)
We report that we estimated the mean proper motion, the full space velocity of five Globular clusters,  Pal 1, Pal2, NGC 1815, NGC 7089, and NGC 7099, using Gaia Early Data Release 3 (Gaia EDR3). We focus on these five clusters to measure proper motion, internal dispersion, and dynamical properties. Also, we have integrated the orbits using the potential of MWPotential2014 for five backyards Gyr. We have derived energy, angular momentum, and orbital properties for each cluster. In addition, we find that there are four metal-poor GCs with metallicity less than -1.1 dex and only one metal-rich GCs with metallicity greater than -1.0 dex. We estimate the distance modulus of these five globular clusters and examine isochrone fitting to the color-magnitude diagram from the PAdova and TRieste Stellar Evolution Code (PARSEC). Among five globular clusters, we have found that the NGC 7099 is the oldest globular cluster age of ∼ 13 Gyr with metallicity ([Fe/H]) of 2.19, whereas the youngest globular cluster we find in our sample is Pal 1 with metallicity ([Fe/H]) of -0.65 and age of ∼ 8 Gyr.